(untitled) (TAJ: Journal of Teachers Association, 2020)
Background: Hand is a highly specialized organ as it has grasping, pinching and hooking function. The hand is prone to domestic and industrial trauma with fingertips being the most frequently injured portion of the hand. Fingertip injuries are commonly seen by emergency physicians Objectives: To see the functional outcome after V-Y flap in fingertip injuries. Methods: Prospective, observational study carried out for 2 years at National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR). Fifteen patients of fingertip injuries were selected for V-Y flap. Results: V-Y plasty was performed in 15 patients who suffered from a transverse amputation of the finger tip. Out of 15 patients, functional outcome was satisfactory (good) in 13(86.7%) cases and unsatisfactory (fair plus poor) in 2 cases (13.3%). 3 patients had postoperative complications. The results showed that V-Y plasty is indicated in transverse amputations through the distal one-third to one-half of the nail bed. Conclusion: Fingertip injury can achieve almost normal sensibility and satisfactory motion by V-Y flap and patients can expect to return to work on average approximately 3 weeks after operation. TAJ 2020; 33(2): 107-112